2021
DOI: 10.1038/s41598-021-81909-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive underpinnings of multidimensional Japanese literacy and its impact on higher-level language skills

Abstract: This study aimed to identify the cognitive underpinnings of Japanese kanji abilities and clarify the contributions of kanji acquisition to the development of higher-level language skills based on a three-dimensional view of kanji abilities encompassing reading accuracy, writing accuracy, and semantic comprehension. First, a series of regression analyses was used to identify the multifactorial models of each dimension of Japanese kanji acquisition. These models suggest that, among basic cognitive skills, naming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 65 publications
(109 reference statements)
1
6
0
Order By: Relevance
“…Our results suggested that word-level comprehension and writing skills acquired during school years underpinned the development of text-level reading and writing proficiency, respectively and dimension-specifically, and the former underlies the latter. This was consistent with accumulated knowledge (Abbott et al, 2010 ; Ahmed et al, 2014 ; Bourke et al, 2014 ; Kim, 2017 , 2020 ; Kim & Graham, 2022 ; Otsuka & Murai, 2021 ; Yeung et al, 2013 ). Furthermore, the significantly large value of the modification index in Model 3 shown with validation data 2 clearly indicated that the contribution of word handwriting skills to text writing proficiency cannot be replaced by the semantic comprehension of words.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our results suggested that word-level comprehension and writing skills acquired during school years underpinned the development of text-level reading and writing proficiency, respectively and dimension-specifically, and the former underlies the latter. This was consistent with accumulated knowledge (Abbott et al, 2010 ; Ahmed et al, 2014 ; Bourke et al, 2014 ; Kim, 2017 , 2020 ; Kim & Graham, 2022 ; Otsuka & Murai, 2021 ; Yeung et al, 2013 ). Furthermore, the significantly large value of the modification index in Model 3 shown with validation data 2 clearly indicated that the contribution of word handwriting skills to text writing proficiency cannot be replaced by the semantic comprehension of words.…”
Section: Discussionsupporting
confidence: 85%
“…The three dimensions of word-level Japanese literacy skills reflect phonological, orthographic, and semantic processing, which are required to master Japanese kanji characters that have multiple pronunciations, visual complexity, and different meanings. The multidimensional nature of word literacy, based on dimension-specific and common cognitive underpinnings (Otsuka & Murai, 2021 ), implies educational or therapeutic strategies may be necessary depending on the dimensions and causes of difficulties in literacy acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations